Malay version of Michigan Hand Outcome Questionnaire: cross culture adaptation and reliability testing in Kuantan Pahang - Lye, Jun Xiong; Khalid, Kamarul Ariffin; Ismail, Raffael; Kow, Ren Yi (2019)
INTRODUCTION: The Michigan Hand Outcomes Questionnaire (MHQ), a self-reported questionnaire for patients with hand disorders, has been widely used globally. It has been cross-culturally adapted into different languages across all continents. Aims of this study were to translate the MHQ into Malay language and to evaluate its reliability in a Malay-speaking population.